Observability-Enhanced PMU Placement Considering Conventional Measurements and Contingencies - M. Esmaili; H. A. Shayanfar; K. Gharani (Iranian Journal of Electrical and Electronic Engineering, 2014)
Phasor Measurement Units (PMUs) are in growing attention in recent power systems because of their paramount abilities in state estimation. PMUs are placed in existing power systems where there are already installed conventional measurements, which can be helpful if they are considered in PMU optimal placement. In this paper, a method is proposed for optimal placement of PMUs incorporating conventional measurements of zero injection buses and branch flow measurements using a permutation matrix. Furthermore, the effect of single branch outage and single PMU failure is included in the proposed method. When a branch with a flow measurement goes out, the network loses one observability path (the branch) and one conventional measurement (the flow measurement). The permutation matrix proposed here is able to model the outage of a branch equipped with a flow measurement or connected to a zero injection bus. Also, measurement redundancy, and consequently measurement reliability, is enhanced without increasing the number of PMUs this implies a more efficient usage of PMUs than previous methods. The PMU placement problem is formulated as a mixed-integer linear programming that results in the global optimal solution. Results obtained from testing the proposed method on four well-known test systems in diverse situations confirm its efficiency.